Production of Potyvirus-Derived Nanoparticles Decorated with a Nanobody in Biofactory Plants - Martí, Maricarmen; Merwaiss, Fernando; Butković, Anamarija; Daròs, José-Antonio (Frontiers in Bioengineering and Biotechnology, 2022)
Viral nanoparticles (VNPs) have recently attracted attention for their use as building blocks for novel materials to support a range of functions of potential interest in nanotechnology and medicine. Viral capsids are ideal for presenting small epitopes by inserting them at an appropriate site on the selected coat protein (CP). VNPs presenting antibodies on their surfaces are considered highly promising tools for therapeutic and diagnostic purposes. Due to their size, nanobodies are an interesting alternative to classic antibodies for surface presentation. Nanobodies are the variable domains of heavy-chain (VHH) antibodies from animals belonging to the family Camelidae, which have several properties that make them attractive therapeutic molecules, such as their small size, simple structure, and high affinity and specificity. In this work, we have produced genetically encoded VNPs derived from two different potyviruses—the largest group of RNA viruses that infect plants—decorated with nanobodies. We have created a VNP derived from zucchini yellow mosaic virus (ZYMV) decorated with a nanobody against the green fluorescent protein (GFP) in zucchini (Cucurbita pepo) plants. As reported for other viruses, the expression of ZYMV-derived VNPs decorated with this nanobody was only made possible by including a picornavirus 2A splicing peptide between the fused proteins, which resulted in a mixed population of unmodified and decorated CPs. We have also produced tobacco etch virus (TEV)-derived VNPs in Nicotiana benthamiana plants decorated with the same nanobody against GFP. Strikingly, in this case, VNPs could be assembled by direct fusion of the nanobody to the viral CP with no 2A splicing involved, likely resulting in fully decorated VNPs. For both expression systems, correct assembly and purification of the recombinant VNPs was confirmed by transmission electron microscope; the functionality of the CP-fused nanobody was assessed by western blot and binding assays. In sum, here we report the production of genetically encoded plant-derived VNPs decorated with a nanobody. This system may be an attractive alternative for the sustainable production in plants of nanobody-containing nanomaterials for diagnostic and therapeutic purposes.